The Effect of Celebrity Endorsement and Brand Image on Purchase Decisions on Elzatta Hijab for Students in Jakarta - Siti Nuryati; Sri Arfani (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this study was to determine the influence of celebrity endorsement and brand image on purchasing decisions for Hijab Elzatta among students in Jakarta. The data were obtained from distributing questionnaires to 34 respondents as a sample using the Likert scale. The data were processed and analyzed using multiple linear regression. The results of the R2 test are 0.459 or 46%, meaning that the purchasing decision variable is explained by the trust and quality variables by 46%. The results of the F test show that f count 13,127> f tabel 3,30, thus simultaneously the celebrity endorsement variable and brand image have a positive and significant influence on the purchasing decision of Elzatta Hijab in students in Jakarta. While the t test results show a significant effect of price on purchasing decisions as evidenced by t count 2.445> ttable 1.690, a significant effect of brand image on purchasing decisions on Elzatta Hijab buyers is evidenced from tcount4.037> t table 1.690. Then the regression equation is obtained Y = 5.742 + 0.236 + 0.422. This means a constant value of 5.742, this shows that if celebrity endorsement and brand image are ignored, then the purchase decision of Elzatta Hijab buyers is 5.742. The regression coefficient of the price variable is 0.236, meaning that each increase in celebrity endorsement is 1 unit, it will be followed by an increase in purchasing decisions for Hijab Elzatta buyers by 0.236. The regression coefficient for brand image variables is 0.422, meaning that each increase in brand image is 1 unit, it will be followed by an increase in purchasing decisions for buyers. Elzatta's Hijab is 0.422. The results of this study are that celebrity endorsement and brand image have a significant effect on the purchasing decisions of Hijab Ellzata buyers among students in Jakarta.